1993
DOI: 10.1177/0261927x93121005
|View full text |Cite
|
Sign up to set email alerts
|

Polarized Semantic Change of Words Associated with Females and Males

Abstract: The present laboratory experiment was inspired by semantic changes reported in etymological studies: Many words that at one time had a positive or neutral connotation became negative when later applied to females. In contrast to this negativity bias, male-associated words underwent a positivity bias. Miller and Swift (1976) referred to the gender-based biases as gender-related semantic polarization. We developed the concept further by distinguishing between gender-stereotypic and gender-non-stereotypic polariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In another unobtrusive study, participants were asked to learn nonsense words that were consistently associated with pictures of women or men (Ng et al, 1993). Results showed that the words acquired connotations aligned with the gender stereotype evoked by the related picture.…”
Section: Effects Of Language On Women's Motivation Self-esteem Performance and Persuasivenessmentioning
confidence: 99%
“…In another unobtrusive study, participants were asked to learn nonsense words that were consistently associated with pictures of women or men (Ng et al, 1993). Results showed that the words acquired connotations aligned with the gender stereotype evoked by the related picture.…”
Section: Effects Of Language On Women's Motivation Self-esteem Performance and Persuasivenessmentioning
confidence: 99%
“…At the establishment of gender and language as a legitimate field of inquiry, work documented the ways language can be understood as ignoring or narrowly defining and demeaning women. Cognitive social psychology has confirmed various psychological implications of sexism in language (Douglas & Sutton, 2014; Ng, Kam Kuen, Weatherall, & Moody, 1993). Social constructionist–informed discourse analysis details how gendered subjectivities and moral orders are produced and resisted (Baxter, 2003).…”
Section: Discussionmentioning
confidence: 96%
“…One of the few opportunities in that area arose in an advanced social psychology class – a group‐project option on ‘sexist language’. Reading on that topic led to my fourth year dissertation – an experimental study on gender biases in word meanings (see Ng, Kam Kuen, Weatherall, & Moody, 1993) and inspired me to further study at postgraduate level.…”
Section: Engaging Feminismmentioning
confidence: 99%